Novel climate–fire–vegetation interactions and their influence on forest ecosystems in the western USA - Liang, Shuang; Hurteau, Matthew D. (Functional ecology, 2023)
Climate, disturbance, vegetation response and their interaction are key factors in predicting the distribution and function of ecosystems across landscapes. A range of factors, operating through different pathways, are amplifying the feedbacks in this three‐way interaction. In the western USA, the relative strength of the influence of climate versus vegetation on fire activity varies spatially, realizing a diversity of fire regimes and fire‐selected species traits under historical conditions of climate–fire–vegetation interactions. Human intervention, via land use and fire‐exclusion, has homogenized frequent‐fire‐adapted forests in terms of structure and composition. Climate change is reinforcing the homogenization directly via increasing temperatures and drought and indirectly through climate‐driven tree mortality. The net effect will be forming novel climate–fire–vegetation interactions that act to homogenize fire regimes and catalyse large‐scale forest loss. While long‐term persistence of tree species in a given location may not be possible due to directional change of climate, slowing the rate of wildfire‐driven forest cover loss and maximizing the in‐situ persistence of a diversity of species will allow forest ecosystems to respond more incrementally to changing climate and provide an opportunity for ecosystem reassembly to occur from a large pool of species. As climate continues to change, management to resist wildfire‐driven forest cover loss may hinge on reducing forest density and creating a higher level of heterogeneity to reach the resistance and resilience exhibited by pre‐fire‐exclusion forests. Management operations should better leverage disturbance while strategically deploying silvicultural treatments to increase managed and prescribed fire. Further research is needed to improve our capacity for quantifying key mechanisms and system responses involved in the climate–fire–vegetation interactions and predicting how best to allocate resources to manage for functional forests. Read the free Plain Language Summary for this article on the Journal blog. Read the free Plain Language Summary for this article on the Journal blog.